High-modulus quasi-solid electrolyte for aqueous zinc ion battery and preparation method of high-modulus quasi-solid electrolyte
By using photo-induced polymerization technology of polyethylene glycol methyl ether methacrylate and other materials in aqueous zinc ion batteries, high-modulus quasi-solid electrolytes were prepared, which solved the problem of insufficient modulus and dendrite, and improved the safety and application potential of the battery.
Patent Information
- Application Number
- CN202411645236.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-11-18
AI Technical Summary
The modulus of aqueous zinc ion quasi-solid electrolyte is relatively low and easy to damage, and it is difficult to suppress dendrites' growth, resulting in insufficient safety and hindering the large-scale application of zinc ion batteries.
Polyethylene glycol methyl ether methacrylate, hydrophobic monomer and crosslinking agent were used to initiate polymerization under the action of photoinitiator to prepare a high-modulus quasi-solid electrolyte precursor, and a high-modulus quasi-solid electrolyte was prepared by soaking zinc salt aqueous solution.
It achieves ultra-high elastic modulus and good conductivity, effectively inhibiting the generation of zinc dendrites, and improving the safety and application potential of the battery.
Smart Images

Figure CN119742465A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aqueous zinc ion battery energy storage, and in particular to a high modulus quasi-solid electrolyte for aqueous zinc ion batteries and a preparation method thereof. Background Art
[0002] With the rapid development of new energy technologies, especially the continuous expansion of markets such as electric vehicles and portable electronic devices, people's demand for high-performance and high-safety batteries is increasing. Although traditional liquid electrolyte batteries have high energy density and ion conductivity, they have safety hazards such as flatulence and leakage, and poor adaptability to the environment. Aqueous zinc-ion batteries have the advantages of high safety, abundant raw material reserves, and environmental friendliness. They have broad application prospects and market potential in the field of large-scale green energy storage.
[0003] However, the development of quasi-solid electrolytes for aqueous zinc-ion batteries still faces many problems that need to be solved. Most zinc-ion quasi-solid electrolytes are hydrogel materials, which have insufficient modulus and are easily damaged. Dendrites on the surface of zinc foil may cause internal short circuits in the battery, which is not safe enough and hinders the large-scale application of zinc-ion batteries. Summary of the invention
[0004] The purpose of the present invention is to provide a high modulus quasi-solid electrolyte for aqueous zinc ion batteries and a preparation method thereof in view of the technical problems faced by the current aqueous zinc ion quasi-solid electrolytes in the background technology, such as low modulus, easy damage, and difficulty in inhibiting dendrite growth.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0006] The present invention provides a high modulus quasi-solid electrolyte for an aqueous zinc ion battery, wherein the high modulus quasi-solid electrolyte is a mixture of a precursor prepared by poly(ethylene glycol) methyl ether methacrylate), a hydrophobic monomer and a cross-linking agent under the initiation of a photoinitiator and a zinc salt aqueous solution. The present invention uses poly(ethylene glycol) methyl ether methacrylate, a hydrophobic monomer and a cross-linking agent to initiate polymerization under the action of a photoinitiator to obtain a precursor, and then soaks the precursor in a zinc salt solution to obtain a quasi-solid electrolyte. The preparation method is simple, the raw materials are easily available, and no organic solvent is required. The obtained quasi-solid electrolyte has an ultra-high elastic modulus and good electrical conductivity, and has great application potential in the field of aqueous zinc ion energy storage.
[0007] Furthermore, the polyethylene glycol methyl ether methacrylate has a molecular weight of 300, 450, 500, 950 or more.
[0008] Furthermore, the hydrophobic monomer is one or more of styrene, benzyl acrylate, benzyl methacrylate, methyl methacrylate, ethyl methacrylate, n-hexyl methacrylate, dodecyl methacrylate, octadecyl methacrylate, and 2-ethylhexyl methacrylate.
[0009] Furthermore, the cross-linking agent is one or more of N,N'-methylenebisacrylamide, diethylene glycol dimethacrylate, and polyethylene glycol dimethacrylate.
[0010] Furthermore, the photoinitiator is one or more of 2-hydroxy-2-methyl-1-phenyl-1-propanone (1173 photoinitiator), phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (819 photoinitiator), 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (2959 photoinitiator), 1-hydroxy-cyclohexyl-phenyl ketone (184 photoinitiator), 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO), 2,4,6-trimethylbenzoylphosphonic acid ethyl ester (TPO-L), benzoin dimethyl ether (DMPA), phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (819 photoinitiator), and 2-methyl-1-[4-methylthiophenyl]-2-morpholinyl-1-propanone (907 photoinitiator).
[0011] Furthermore, the zinc salt in the zinc salt aqueous solution is one or more of zinc chloride, zinc sulfate, zinc trifluoromethanesulfonate, zinc acetate, zinc perchlorate, and zinc bis(trifluoromethylsulfonyl)imide.
[0012] The present invention also provides a method for preparing the high modulus quasi-solid electrolyte for aqueous zinc ion batteries, the preparation method comprising: uniformly mixing polyethylene glycol methyl ether methacrylate, a hydrophobic monomer, a crosslinking agent and a photoinitiator, injecting the mixture into a mold, initiating polymerization under ultraviolet light to obtain a precursor; and immersing the precursor in a zinc salt aqueous solution to obtain the high modulus quasi-solid electrolyte.
[0013] Furthermore, the molar ratio of the polyethylene glycol methyl ether methacrylate, the hydrophobic monomer, the crosslinking agent and the photoinitiator is 1:0.5-40:0.001-0.01:0.01-0.02; preferably, the molar ratio of the polyethylene glycol methyl ether methacrylate, the hydrophobic monomer, the crosslinking agent and the photoinitiator is 1:10:0.005:0.02; preferably, the mixing time is 10-40 min.
[0014] Furthermore, the ultraviolet light irradiation time is 0.5 to 3 hours.
[0015] Furthermore, the concentration of the zinc salt aqueous solution is 0.5 to 3 M; preferably, the soaking time is 6 to 36 hours.
[0016] Compared with the prior art, the present invention has the following beneficial effects:
[0017] The present invention provides a high modulus quasi-solid electrolyte for aqueous zinc ion batteries and a preparation method thereof. A quasi-solid electrolyte precursor for aqueous zinc ion batteries is prepared by simple free radical polymerization, and a high modulus quasi-solid electrolyte is prepared by solution immersion. Due to the aggregation and hardening of hydrophobic units, the material can effectively bear external forces, and has an ultra-high elastic modulus, which inhibits the generation of zinc dendrites; based on the movement of a large number of polyethylene glycol chain segments, Zn 2+ The electrolyte can be quickly transmitted and has good electrical conductivity. The preparation method provided by the invention is simple, effective, low-cost, and conducive to large-scale production, providing a certain reference for promoting the application of zinc ion batteries in the field of energy storage. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 is a schematic diagram of a quasi-solid electrolyte prepared in an embodiment of the present invention;
[0020] Figure 2 is an optical picture of a quasi-solid electrolyte prepared in Example 3 of the present invention before and after hardening and pulling a heavy object;
[0021] Figure 3 This is an optical picture of the changes in volume, softness, and conductive properties of the quasi-solid electrolyte prepared in Example 6 of the present invention before and after immersion;
[0022] Figure 4 3 is the stress-strain curve of the quasi-solid electrolyte prepared in Example 6 of the present invention after immersion. DETAILED DESCRIPTION
[0023] The present invention will be further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.
[0024] It should be noted that the purpose of the following implementation cases is to enable people in this field to understand the content of the present invention and implement it accordingly, and it cannot be used to limit the scope of protection of the present invention. All equivalent changes or modifications made according to the spirit of the present invention should be included in the scope of protection of the present invention.
[0025] Hereinafter, specific embodiments of the present invention will be described in detail with reference to the accompanying drawings. According to these detailed descriptions, those skilled in the art can clearly understand the present invention and can implement the present invention. Without violating the principles of the present invention, the features in different embodiments can be combined to obtain new implementations, or certain features in certain embodiments can be replaced to obtain other preferred implementations.
[0026] Example 1
[0027] The high modulus quasi-solid electrolyte in this embodiment is polyethylene glycol methyl ether methacrylate (M n =500), a mixture of a hydrophobic monomer, a crosslinking agent, a photoinitiator, a zinc salt and water, specifically methyl methacrylate as the hydrophobic monomer, diethylene glycol dimethacrylate as the crosslinking agent, 2-hydroxy-2-methyl-1-phenyl-1-propanone as the photoinitiator, and zinc sulfate as the zinc salt.
[0028] The preparation method of the high modulus quasi-solid electrolyte in this embodiment has the following specific steps:
[0029] In a flask equipped with a stirrer, 0.5 g of polyethylene glycol methyl ether methacrylate, 1.5 g of methyl methacrylate, 0.02 g of diethylene glycol dimethacrylate, and 0.01 g of 2-hydroxy-2-methyl-1-phenyl-1-propanone were added, mixed evenly, and injected into a rectangular mold, and irradiated under ultraviolet light for 2 hours. After the reaction was completed, the obtained sample was immersed in a 1M zinc sulfate aqueous solution for 6 hours to obtain a high modulus quasi-solid electrolyte.
[0030] Example 2
[0031] The high modulus quasi-solid electrolyte in this embodiment is polyethylene glycol methyl ether methacrylate (M n =500), a mixture of a hydrophobic monomer, a crosslinking agent, a photoinitiator, a zinc salt and water, specifically ethyl methacrylate as the hydrophobic monomer, diethylene glycol dimethacrylate as the crosslinking agent, phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide as the photoinitiator, and zinc perchlorate as the zinc salt.
[0032] The preparation method of the high modulus quasi-solid electrolyte in this embodiment has the following specific steps:
[0033] In a flask equipped with a stirrer, add 0.95g of polyethylene glycol methyl ether methacrylate, 1.14g of ethyl methacrylate, 0.021g of diethylene glycol dimethacrylate, and 0.021g of phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide, mix well, and inject into a rectangular mold, and irradiate under ultraviolet light for 1 hour. After the reaction is completed, the obtained sample is immersed in a 1M zinc perchlorate aqueous solution for 12 hours to obtain a high modulus quasi-solid electrolyte.
[0034] Example 3
[0035] The high modulus quasi-solid electrolyte in this embodiment is polyethylene glycol methyl ether methacrylate (M n=300), a mixture of a hydrophobic monomer, a crosslinking agent, a photoinitiator, a zinc salt and water, specifically styrene is the hydrophobic monomer, N,N'-methylenebisacrylamide is the crosslinking agent, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone is the photoinitiator, and zinc acetate is the zinc salt.
[0036] The preparation method of the high modulus quasi-solid electrolyte in this embodiment has the following specific steps:
[0037] In a flask equipped with a stirrer, add 3g of polyethylene glycol methyl ether methacrylate, 2.08g of styrene, 0.005g of N,N'-methylenebisacrylamide, and 0.05g of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, mix well, and inject into a rectangular mold, and irradiate under ultraviolet light for 3 hours. After the reaction is completed, the obtained sample is immersed in a 1M zinc acetate aqueous solution for 24 hours to obtain a high modulus quasi-solid electrolyte. The optical pictures of the prepared quasi-solid electrolyte before and after hardening are shown in Figure 2. Figure 2 As shown, from Figure 2 It can be seen that the polymer before hardening is relatively soft, and even after a large deformation, it is still unable to lift heavy objects; while the electrolyte after hardening can easily lift a 2kg weight, which intuitively demonstrates the effect of water-induced hardening.
[0038] Example 4
[0039] The high modulus quasi-solid electrolyte in this embodiment is polyethylene glycol methyl ether methacrylate (M n =450), a mixture of a hydrophobic monomer, a crosslinking agent, a photoinitiator, a zinc salt and water, specifically benzyl acrylate as the hydrophobic monomer, N,N'-methylenebisacrylamide as the crosslinking agent, 2,4,6-trimethylbenzoyldiphenylphosphine oxide as the photoinitiator, and bis(trifluoromethylsulfonyl)imide zinc as the zinc salt.
[0040] The preparation method of the high modulus quasi-solid electrolyte in this embodiment has the following specific steps:
[0041] In a flask equipped with a stirrer, add 0.9g of polyethylene glycol methyl ether methacrylate, 1.62g of benzyl acrylate, 0.013g of N,N'-methylenebisacrylamide, and 0.013g of 2,4,6-trimethylbenzoyldiphenylphosphine oxide, mix well, and inject into a rectangular mold, and irradiate under ultraviolet light for 0.5 hours. After the reaction is completed, the obtained sample is immersed in a 1M bis(trifluoromethylsulfonyl)imide zinc aqueous solution for 24 hours to obtain a high modulus quasi-solid electrolyte.
[0042] Example 5
[0043] The high modulus quasi-solid electrolyte in this embodiment is polyethylene glycol methyl ether methacrylate (M n=950), a mixture of a hydrophobic monomer, a crosslinking agent, a photoinitiator, a zinc salt and water, specifically benzyl methacrylate as the hydrophobic monomer, polyethylene glycol dimethacrylate as the crosslinking agent, 1-hydroxy-cyclohexyl-phenyl ketone as the photoinitiator, and zinc trifluoromethanesulfonate as the zinc salt.
[0044] The preparation method of the high modulus quasi-solid electrolyte in this embodiment has the following specific steps:
[0045] 0.95g of polyethylene glycol methyl ether methacrylate, 1.76g of benzyl methacrylate, 0.027g of polyethylene glycol dimethacrylate, and 0.014g of 1-hydroxy-cyclohexyl-phenyl ketone were added to a flask equipped with a stirrer, mixed evenly, and injected into a rectangular mold, and irradiated under ultraviolet light for 3 hours. After the reaction was completed, the obtained sample was immersed in a 1M aqueous solution of zinc trifluoromethanesulfonate for 24 hours to obtain a high modulus quasi-solid electrolyte.
[0046] Example 6
[0047] The high modulus quasi-solid electrolyte in this embodiment is polyethylene glycol methyl ether methacrylate (M n =500), a mixture of a hydrophobic monomer, a crosslinking agent, a photoinitiator, a zinc salt and water, specifically, dodecyl methacrylate is the hydrophobic monomer, polyethylene glycol dimethacrylate is the crosslinking agent, ethyl 2,4,6-trimethylbenzoylphosphonate is the photoinitiator, and zinc sulfate is the zinc salt.
[0048] The preparation method of the high modulus quasi-solid electrolyte in this embodiment has the following specific steps:
[0049] In a flask equipped with a stirrer, add 0.5g of polyethylene glycol methyl ether methacrylate, 2.54g of dodecyl methacrylate, 0.03g of polyethylene glycol dimethacrylate, and 0.06g of ethyl 2,4,6-trimethylbenzoylphosphonate, mix well, and inject into a rectangular mold. Irradiate under ultraviolet light for 0.5 hours. After the reaction is completed, the obtained sample is soaked in a zinc sulfate aqueous solution for 12 hours to obtain a high modulus quasi-solid electrolyte. The optical pictures of the changes in volume, softness, and conductive properties of the prepared quasi-solid electrolyte before and after immersion are shown in Figure 2. Figure 3 As shown, from Figure 3 It can be seen that after the polymer is immersed in the solution, its volume increases due to swelling, and the sample after immersion has an obvious hardening effect; the dry sample is not conductive and cannot be turned on when connected to the circuit, while the sample after immersion contains ions and can be turned on when connected to the circuit, and the red LED is lit. Figure 4 The stress-strain curve of the sample is shown. The tensile strength of the quasi-solid electrolyte is as high as 5MPa and the Young's modulus is 120MPa, which are much higher than those of common quasi-solid electrolytes.
[0050] Example 7
[0051] The high modulus quasi-solid electrolyte in this embodiment is polyethylene glycol methyl ether methacrylate (M n =450), a mixture of a hydrophobic monomer, a crosslinking agent, a photoinitiator, a zinc salt and water, specifically octadecyl methacrylate as the hydrophobic monomer, N,N'-methylenebisacrylamide as the crosslinking agent, 2-hydroxy-2-methyl-1-phenyl-1-propanone as the photoinitiator, and zinc sulfate as the zinc salt.
[0052] The preparation method of the high modulus quasi-solid electrolyte in this embodiment has the following specific steps:
[0053] 0.45g of polyethylene glycol methyl ether methacrylate, 3.39g of octadecyl methacrylate, 0.0384g of N,N'-methylenebisacrylamide, and 0.0182g of 2-hydroxy-2-methyl-1-phenyl-1-propanone were added to a flask equipped with a stirring bar, mixed evenly, and injected into a rectangular mold, and irradiated under ultraviolet light for 1 hour. After the reaction was completed, the obtained sample was immersed in a zinc sulfate aqueous solution for 36 hours to obtain a high modulus quasi-solid electrolyte.
[0054] Example 8
[0055] The high modulus quasi-solid electrolyte in this embodiment is polyethylene glycol methyl ether methacrylate (M n =450), a mixture of a hydrophobic monomer, a crosslinking agent, a photoinitiator, a zinc salt and water, specifically 2-ethylhexyl methacrylate as the hydrophobic monomer, N,N'-methylenebisacrylamide as the crosslinking agent, 2-hydroxy-2-methyl-1-phenyl-1-propanone as the photoinitiator, and zinc sulfate as the zinc salt.
[0056] The preparation method of the high modulus quasi-solid electrolyte in this embodiment has the following specific steps:
[0057] 0.3g of polyethylene glycol methyl ether methacrylate, 5.95g of 2-ethylhexyl methacrylate, 0.0063g of N,N'-methylenebisacrylamide, and 0.0625g of 2-hydroxy-2-methyl-1-phenyl-1-propanone were added to a flask equipped with a stirrer, mixed evenly, and injected into a rectangular mold, and irradiated under ultraviolet light for 0.5 hours. After the reaction was completed, the obtained sample was immersed in a zinc sulfate aqueous solution for 24 hours to obtain a high modulus quasi-solid electrolyte.
[0058] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the contents of the present invention and implement them accordingly. They cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
[0059] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A high modulus quasi-solid electrolyte for aqueous zinc ion batteries, characterized in that: The high modulus quasi-solid electrolyte is a mixture of a precursor prepared by polyethylene glycol methyl ether methacrylate, a hydrophobic monomer and a cross-linking agent under the initiation of a photoinitiator and a zinc salt aqueous solution.
2. The high modulus quasi-solid electrolyte for aqueous zinc ion batteries according to claim 1, characterized in that The polyethylene glycol methyl ether methacrylate has a molecular weight of 300, 450, 500, 950 or more.
3. The high modulus quasi-solid electrolyte for aqueous zinc ion batteries according to claim 1, characterized in that The hydrophobic monomer is one or more of styrene, benzyl acrylate, benzyl methacrylate, methyl methacrylate, ethyl methacrylate, n-hexyl methacrylate, dodecyl methacrylate, octadecyl methacrylate, and 2-ethylhexyl methacrylate.
4. The high modulus quasi-solid electrolyte for aqueous zinc ion batteries according to claim 1, characterized in that The cross-linking agent is one or more of N,N'-methylenebisacrylamide, diethylene glycol dimethacrylate, and polyethylene glycol dimethacrylate.
5. The high modulus quasi-solid electrolyte for aqueous zinc ion batteries according to claim 1, characterized in that: The photoinitiator is one or more of 2-hydroxy-2-methyl-1-phenyl-1-propanone, phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, 1-hydroxy-cyclohexyl-phenyl ketone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 2,4,6-trimethylbenzoylphosphonic acid ethyl ester, benzoin dimethyl ether, phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide, and 2-methyl-1-[4-methylthiophenyl]-2-morpholinyl-1-propanone.
6. The high modulus quasi-solid electrolyte for aqueous zinc ion batteries according to claim 1, characterized in that: The zinc salt in the zinc salt aqueous solution is one or more of zinc chloride, zinc sulfate, zinc trifluoromethanesulfonate, zinc acetate, zinc perchlorate, and bis(trifluoromethylsulfonyl)imide zinc.
7. The method for preparing a high modulus quasi-solid electrolyte for an aqueous zinc ion battery according to any one of claims 1 to 6, characterized in that: The preparation method comprises: Polyethylene glycol methyl ether methacrylate, a hydrophobic monomer, a crosslinking agent and a photoinitiator are uniformly mixed and injected into a mold, and polymerization is initiated under ultraviolet light to obtain a precursor; the precursor is immersed in a zinc salt aqueous solution to obtain the high modulus quasi-solid electrolyte.
8. The method for preparing a high modulus quasi-solid electrolyte for an aqueous zinc ion battery according to claim 7, characterized in that: The molar ratio of the polyethylene glycol methyl ether methacrylate, the hydrophobic monomer, the crosslinking agent and the photoinitiator is 1:0.5-40:0.001-0.01:0.01-0.02; Preferably, the molar ratio of the polyethylene glycol methyl ether methacrylate, the hydrophobic monomer, the crosslinking agent and the photoinitiator is 1:10:0.005:0.02; Preferably, the mixing time is 10 to 40 minutes.
9. The method for preparing a high modulus quasi-solid electrolyte for an aqueous zinc ion battery according to claim 7, characterized in that: The ultraviolet light irradiation time is 0.5 to 3 hours.
10. The method for preparing a high modulus quasi-solid electrolyte for an aqueous zinc ion battery according to claim 7, characterized in that: The concentration of the zinc salt aqueous solution is 0.5 to 3 M; Preferably, the soaking time is 6 to 36 hours.
Citation Information
Patent Citations
Polymer electrolyte and preparation method and application thereof
CN112979875A
Method for in-situ preparation of solid electrolyte based on local high-concentration precursor solution
CN114361603A
Rechargeable battery with aqueous-based electrolyte
US20220045368A1
Anion conducting polymer electrolyte membranes by ultraviolet-light curing for quasi-solid-state zinc-air batteries
WO2023148782A1